Factors Affecting the Work Readiness of Vocational School Students: A Systematic Literature Review - Suroto, Suroto; Sunyono, Sunyono; Sukirlan, Muhammad; Winatha, I Komang; Yuliyanto, Riyan; Rahmawati, Fanni (Jurnal Pendidikan Progresif, 2024)
Factors Affecting the Work Readiness of Vocational School Students: A Systematic Literature Review. Objectives: This study aims to comprehensively identify and analyze the factors affecting the work readiness of vocational school students, employing a systematic literature review approach. It seeks to provide comprehensive insights into individual, educational, and contextual elements that shape students' preparedness for transitioning into the workforce. Methods: The research employs a systematic literature review methodology, analyzing relevant academic articles and reports published between 2015 and 2024. Sources were selected based on predefined criteria emphasizing their relevance to vocational education, work readiness, and factors shaping students' transition to employment. Key themes were identified and synthesized to construct a comprehensive understanding of the topic. Findings: The study identifies three principal dimensions influencing work readiness. First, individual factors, including motivation, interpersonal skills, self-efficacy, self-regulation, and soft skills, are crucial in equipping students to adapt successfully to professional environments. Second, the learning process, including experiential activities like internships and teaching factories, enhances students’ technical and non-technical skills by bridging the gap between theoretical knowledge and practical application. Third, contextual factors—such as socioeconomic status, regional disparities, and social support systems—substantially impact students’ access to resources and opportunities, thereby shaping their career preparedness. Additionally, regional disparities in school-industry partnerships underscore the need for localized interventions to address these gaps. Conclusion: Work readiness among vocational school students is a multifaceted construct shaped by individual characteristics, practical learning experiences, and contextual influences. Developing targeted strategies, such as integrating industry-relevant practical learning models and fostering collaboration among stakeholders, can significantly enhance students’ preparedness for entering the workforce. Policymakers and educators are encouraged to address resource and opportunity disparities to ensure equitable outcomes for all students. Keywords: contextual factors, individual factors, systematic literature review, vocational school students, work readiness.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024124